European IPF Patient Charter: unmet needs and a call to action for healthcare policymakers. Issue 2 (19th November 2015) - Bonella, Francesco; Wijsenbeek, Marlies; Molina-Molina, Maria; Duck, Annette; Mele, Rosalba; Geissler, Klaus; Wuyts, Wim
Patient advocacy groups play an important role in supporting patients with chronic diseases and promoting better care. The aim of this patient–physician initiative was to gather perceptions from European idiopathic pulmonary fibrosis (IPF) patient advocacy groups regarding inequalities and unmet needs in IPF care, in order to develop a Patient Charter to advocate for better care. In total, 11 European patient advocacy groups were interviewed regarding the care of patients with IPF in their countries. Interview feedback was presented to a Working Group including patient advocacy group representatives and IPF specialists; key areas of agreement were developed into the European IPF Patient Charter. The interviews identified five key themes that fed into the final Charter: the need for improved diagnosis, treatment access, holistic care, disease awareness and palliative care. The final Charter was endorsed by patient advocacy groups and presented to 26 Members of the European Parliament in September 2014. It has received >8900 signatures to date. This patient–physician initiative highlights the inequalities and unmet needs in IPF care across Europe, and demonstrates how this insight can inform the development of a Patient Charter, designed as a call to action for healthcare policymakers to drive improvement in European IPF care. European IPF Patient Charter details unmet needs in IPF and presents a call to action for healthcare policymakers http://ow.ly/Td8rj